2019
DOI: 10.1155/2019/2842313
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Survey of Decreased Blood Flow Rate in Continuous Renal Replacement Therapy: A Retrospective Observational Study

Abstract: Background Continuous renal replacement therapy (CRRT) is an essential procedure for patients with acute kidney injury in intensive care. It is important to maintain an adequate blood flow rate during CRRT. Several previous studies have reported the relationships between blood flow rate and filter lifespan, or circuit life, in CRRT. Here, we aim at elucidating the incidence and factors associated with a decreased blood flow rate in CRRT. Methods This is a retrospective observational study. From January 2014 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
1
1
Order By: Relevance
“… 21 , 22 A retrospective observational clinical survey from Japan also found sepsis (32.8 %) or severe infectious disease as the main reason for initiating CRRT, followed by heart failure (28.6 %), surgery (21 %), hepatic failure (1.7 %) and renal failure (4.2 %). 23 In contrast, acute coronary syndrome with cardiogenic shock (30.2 %) was the major cause of AKI in our study. An Indian study also reported that out of 22 patients who were due for CRRT, sepsis was present in 68.2%, CKD in 36.4% and diabetes in 27.3%.…”
Section: Discussioncontrasting
confidence: 63%
“… 21 , 22 A retrospective observational clinical survey from Japan also found sepsis (32.8 %) or severe infectious disease as the main reason for initiating CRRT, followed by heart failure (28.6 %), surgery (21 %), hepatic failure (1.7 %) and renal failure (4.2 %). 23 In contrast, acute coronary syndrome with cardiogenic shock (30.2 %) was the major cause of AKI in our study. An Indian study also reported that out of 22 patients who were due for CRRT, sepsis was present in 68.2%, CKD in 36.4% and diabetes in 27.3%.…”
Section: Discussioncontrasting
confidence: 63%
“…Besides the varying levels of shear stress, different flow patterns are also present in the dynamic environment of the bloodstream [ 33 , 34 ]. To investigate the influence of uptake under different flow patterns, the parallel-plate flow chamber that can mimic the flow dynamics of vascular bifurcation or straight arteries was used to evaluate the uptake of RBCEVs by endothelial cells under normal shear stress with laminar flow (NSS) and OSS, respectively ( Fig.…”
Section: Resultsmentioning
confidence: 99%